Comparison analysis of muscle activity of the upper imb muscles and erector spinae in female archery players according to the success and failure of shoot - Choi, D. S. (Korean Journal of Sport Science, 2020)
The purpose of this study was to compare muscle activity of the upper limbs muscles and erector spinae in female archery players according to the success and failure of shoot. In this study, the subject were consisted of the 9 female archers to investigate the muscle activity. Draw arm biceps brachii (BB), flexor digitorum superficialis (FDS), middle deltoid (MD), trapezius (TRA), triceps brachii (TB), erector spinae (ES) and bow arm trapezius (TRA), triceps brachii (TB), erector spine (ES) of muscle activity was examined with electromyography (EMG) equipment (Noraxon, USA). The results were as follows. First, in the FDS muscle activity of draw arm, lowest score was statistically significantly higher then highest score in the shooting phase. Second, in the TB muscle activity of bow arm, lowest score was statistically significantly higher then highest score in the shooting phase. And also, in the TRA muscle activity of bow arm, lowest score was statistically significantly higher then highest score the shooting phase. In conclusion, this study was suggested that the female archery players was difference muscle activity of particular muscle in the shooting phase according to the success and failure of shoot.